Students can Download Maths Chapter 3 Algebra Ex 3.3 Questions and Answers, Notes Pdf, Samacheer Kalvi 8th Maths Book Solutions Guide Pdf helps you to revise the complete Tamilnadu State Board New Syllabus and score more marks in your examinations.

## Tamilnadu Samacheer Kalvi 8th Maths Solutions Term 1 Chapter 3 Algebra Ex 3.3

**8th Maths Algebra Exercise 3.3 Question 1.**

Expand

(i) (3m + 5)^{2}

(ii) (5p – 1)^{2}

(iii) (2n – 1)(2n + 3)

(iv) 4p^{2} – 25q^{2}

Solution:

(i) (3m + 5)^{2}

Comparing (3m + 5)^{2} with (a + b)^{2} we have a = 3m and b = 5

(a + b)^{2} = a^{2} + 2 ab + b^{2}

(3m + 5)^{2} = (3m)^{2} + 2 (3m) (5) + 5^{2}

= 3^{2}m^{2} + 30m + 25 = 9m^{2} + 30m +25

(ii) (5p – 1)^{2}

Comparing (5p – 1)^{2} with (a – b)^{2} we have a = 5p and b = 1

(a – b)^{2} = a^{2} – 2ab + b^{2}

(5p – 1)^{2} = (5p)^{2} – 2 (5p) (1) + 1^{2}

= 5^{2}p^{2} – 10p + 1 = 25p^{2} – 10p + 1

(iii) (2n – 1)(2n + 3)

Comparing (2n – 1) (2n + 3) with (x + a) (x + b) we have a = -1; b = 3

(x + a) (x + b) = x^{2} + (a + b)x + ab

(2n +(- 1)) (2n + 3) = (2n)^{2} + (-1 + 3)2n + (-1) (3)

= 2^{2}n^{2} + 2 (2n) – 3 = 4n^{2} + 4n – 3

(iv) 4p^{2} – 25q^{2} = (2p)^{2} – (5q)^{2}

Comparing (2p)^{2} – (5q)^{2} with a^{2} – b^{2} we have a = 2p and b = 5q

(a^{2} – b^{2}) = (a + b)(a – b) = (2p + 5q) (2p – 5q)

**Maths Chapter 3 Exercise 3.3 Class 8 Question 2.**

Expand

(i) (3 + m)^{3}

(ii) (2a + 5)^{3}

(iii) (3p + 4q)^{3}

(iv) (52)^{3}

(v) (104)^{3}

Solution:

(i) (3 + m)^{3}

Comparing (3 + m)^{3} with (a + b)^{3} we have a = 3; b = m

(a + b)^{3} = a^{2} + 3a^{2}b + 3 ab^{2} + b^{3}

(3 + m)^{3} = 3^{3} + 3(3)^{2} (m) + 3 (3) m^{2} + m^{3}

= 27 + 27m + 9m^{2} + m^{3} = m^{3} + 9 m^{2} + 27m + 27

(ii) (2a + 5)^{3}

Comparing (2a + 5)^{3} with (a + b)^{3} we have a = 2a, b = 5

(a + b)^{3} = a^{3} + 3a^{2}b + 3ab^{2} + b^{3} = (2a)^{3} + 3(2a)^{2} 5 + 3 (2a) 5^{2} + 5^{3}

= 2^{3}a^{3} + 3(2^{2}a^{2}) 5 + 6a (25) + 125

= 8a^{3}+ 60a^{2} + 150a + 125

(iii) (3p + 4q)^{3}

Comparing (3p + 4q)^{3} with (a + b)^{3} we have a = 3p and b = 4q

(a + b) ^{3} = a^{3} + 3a^{2}b + 3ab^{2} + b^{3}

(3p + 4q)^{3} = (3p)^{3} + 3(3p)^{2} (4q) + 3(3p)(4q)^{2} + (4q)^{3}

= 3^{3}p^{3} +3 (9p^{2}) (4q) + 9p (16q^{2}) + 43q^{3}

= 27p^{3} + 108p^{2}q + 144pq^{2} + 64q^{3}

(iv) (52)^{3} = (50 + 2)^{3}

Comparing (50 + 2)^{3} with (a + b)^{3} we have a = 50 and b = 2

(a + b)^{3} = a^{3} + 3 a^{2}b + 3 ab^{2} + b^{3}

(50 + 2)^{3} = 50^{3} + 3 (50)^{2}2 + 3 (50)(2)^{2} + 2^{3}

52^{3} = 125000 + 6(2,500) + 150(4) + 8

= 1,25,000 + 15,000 + 600 + 8

52^{3} = 1,40,608

(v) (104)^{3} = (100 + 4)^{3}

Comparing (100 + 4)^{3} with (a + b)^{3} we have a = 100 and b = 4

(a + b)^{3} = a^{3} + 3 a^{2}b + 3 ab^{2} + b^{3}

(100 + 4)^{3} = (100)^{3} + 3 (100)^{2} (4) + 3 (100) (4)^{2} + (4)^{3}

= 10,00,000 + 3(10000) 4 + 300 (16) + 64

= 10,00,000 + 1,20,000 + 4,800 + 64 = 11,24,864

**Samacheer Kalvi 8 Maths Question 3.**

Expand

(i) (5 – x)^{3}

(ii) (2x – 4y)^{3}

(iii) (ab – c)^{3}

(iv) (48)^{3}

(v) (97xy)^{3}

Solution:

(i) (5 – x)^{3}

Comparing (5 – x)^{3} with (a – b)^{3} we have a = 5 and b = x

(a – b)^{3} = a^{3} – 3a^{2}b + 3ab^{2} – b^{3}

(5 – x)^{3} = 5^{3} – 3 (5)^{2} (x) + 3(5)(x^{2}) – x^{3}

= 125 – 3(25)(x) + 15x^{2} – x^{3} = 125

(ii) (2x – 4y)^{3}

Comparing (2x – 4y)^{3} with (a – b)^{3} we have a = 2x and b = 4y

(a – b)^{3} = a^{3} – 3a^{2}b + 3ab^{3} – b^{3}

(2x – 4y)^{3} = (2x)^{3} – 3(2x)^{2} (4y) + 3(2x) (4y)^{2} – (4y)^{3}

= 2^{3}x^{3} – 3(2^{2}x^{2}) (4y) + 3(2x) (4^{2}y^{2}) – (4^{3}y^{3})

= 8x^{3} – 48x^{2}y + 96xy^{2} – 64y^{3}

(iii) (ab – c)^{3}

Comparing (ab – c)^{3} with (a – b)^{3} we have a = ab and b = c

(a – b)^{3} = a^{3} – 3a^{2}b + 3ab^{2} – b^{3}

(ab – c)^{3} = (ab)^{3} – 3 (ab)^{2} c + 3 ab (c)^{2} – c^{3}

= a^{3}b^{3} – 3(a^{2}b^{2}) c + 3abc^{2} – c^{3}

= a^{3}b^{3} – 3a^{2}b^{2} c + 3abc^{2} – c^{3}

(iv) (48)^{3} = (50 – 2)^{3}

Comparing (50 – 2)^{3} with (a – b)^{3} we have a = 50 and b = 2

(a – b)^{3} = a^{3} – 3a^{2}b + 3ab^{2} – b^{3}

(50 – 2)^{3} = (50)^{3} – 3(50)^{2}(2) + 3 (50)(2)^{2} – 2^{3}

= 1,25,000 – 15000 + 600 – 8 = 1,10,000 + 592

= 1,10,592

(v) (97xy)^{3}

= 97^{3} x^{3} y^{3} = (100 – 3)^{3} x^{3}y^{3}

Comparing (100 – 3)^{3} with (a – b)^{3} we have a = 100, b = 3

(a – b)^{3} = a^{3} – 3a^{2}b + 3ab^{2} – b^{3}

(100 – 3)^{3} = (100)^{3} – 3(100)^{2} (3) + 3 (100)(3)^{2} – 3^{3}

97^{3} = 10,00,000 – 90000 + 2700 – 27

97^{3} = 910000 + 2673

97^{3} = 912673

97x^{3}y^{3} = 912673x^{3}y^{3}

**Samacheer Kalvi 8th Maths Book Question 4.**

Simplify (i) (5y + 1)(5y + 2)(5y + 3)

(ii) (p – 2)(p + 1)(p – 4)

Solution:

(i) (5y + 1) (5y + 2) (5y + 3)

Comparing (5y + 1) (5y + 2) (5y + 3) with (x + a) (x + b) (x + c) we have x = 5y ; a = 1; b = 2 and c = 3.

(x + a) (x + b) (x + c) = x^{3} + (a + b + c) x^{2} (ab + bc + ca) x + abc

= (5y)^{3} + (1 + 2 + 3) (5y)^{2} + [(1) (2) + (2) (3) + (3) (1)] 5y + (1)(2) (3)

= 5^{3}y^{3} + 6(5^{2}y^{2}) + (2 + 6 + 3)5y + 6

= 125^{3} + 150y^{2} + 55y + 6

(ii) (p – 2)(p + 1)(p – 4) = (p + (-2))0 +1)(p + (-4))

Comparing (p – 2) (p + 1) (p – 4) with (x + a) (x + b) (x + c) we have x = p ; a = -2; b = 1 ; c = -4.

(x + a) (x + b) (x + c) = x^{3} + (a + b + c) x^{2} + (ab + be + ca) x + abc

= p^{3} + (-2 + 1 + (-4))p^{2} + ((-2) (1) + (1) (-4) (-4) (-2)p + (-2) (1) (-4)

= p^{3} + (-5 )p^{2} + (-2 + (-4) + 8)p + 8

= p^{3} – 5p^{2} + 2p + 8

**Samacheer Kalvi Guru 8th Maths Question 5.**

Find the volume of the cube whose side is (x + 1) cm.

Solution:

Given side of the cube = (x + 1) cm

Volume of the cube = (side)^{3} cubic units = (x + 1)^{3} cm^{3}

We have (a + b)^{3} = (a^{3} + 3a^{2}b + 3ab^{2} + b^{3}) cm^{3}

(x + 1)^{3} = (x^{3} + 3x^{2} (1) + 3x (1)^{2} + 1^{3}) cm^{3}

Volume = (x^{3} + 3x^{2} + 3x + 1) cm^{3}

**Samacheerkalvi.Guru 8th Maths Question 6.**

Find the volume of the cuboid whose dimensions are (x + 2),(x – 1) and (x – 3).

Solution:

Given the dimensions of the cuboid as (x + 2), (x – 1) and (x – 3)

∴ Volume of the cuboid = (l × b × h) units^{3}

= (x + 2) (x – 1) (x – 3) units^{3}

We have (x + a) (x + b) (x + c) = x^{3} + (a + b + c) x^{2} + (ab + bc+ ca)x + abc

∴ (x + 2)(x – 1) (x – 3) = x^{3} + (2 – 1 – 3)x^{2} + (2 (-1) + (-1) (-3) + (-3) (2)) x + (2)(-1) (-3)

x^{3} – 2x^{2} + (-2 + 3 – 6)x + 6

Volume = x^{3} – 2x^{2} – 5x + 6 units^{3}